Isolation, structural characterisation and evaluation of cytotoxic activity of natural products from selected South African marine red algae - Knott, Michael George (Rhodes University, Faculty of Pharmacy, Pharmacy, 2012)
The medicinal chemistry of selected marine algae indigenous to South Africa was investigated. Following the isolation and characterisation of a number of new and known compounds, the associated in vitro cytotoxic profiles of these new compounds was investigated. Plocamium maxillosum yielded two new cyclic polyhalogenated monoterpenes which were characterised as 2E-chloromethine-4E-chlorovinyl-4-methyl-5-cyclohexen-1-one (2.1) and 2Z-chloromethine-4E-chlorovinyl-4-methyl-5-cyclohexen-1-one (2.2) on the basis of one and two dimensional NMR spectroscopic data and MS analysis. These compounds were also found to have good cytotoxic activity against breast cancer cell lines. Although these compounds are based on a regular monoterpene skeleton, they represent an uncommon feature not often seen in cyclic halogenated monoterpenes from marine algae. Plocamium robertiae yielded one new cyclic polyhalogenated monoterpene identified as 4,5- dibromo-5-chloromethyl-1-chlorovinyl-2-chloro-methylcyclohexane (2.6) and one known compound called 2,4-dichloro-1-chlorovinyl-1-methylcyclohexane-5-ene or Plocamene D (2.9). Portieria hornemannii was collected from Port Edward in Natal and yielded three new compounds, namely; 3Z-1,6-dibromo-3-(bromomethylidene)-2,7-dichloro-7-methyloctane (3.1), 1E,3Z-1,6-dibromo-3-(bromomethylidene)-7-chloro-7-methyloct-1-ene (3.2), 1Z,3Z- 1,6-dibromo-3-(bromomethylidene)-7-chloro-7-methyloct-1-ene (3.3), and one known compound, namely; 3S,6R-6-bromo-3-(bromomethyl)-3,7-dichloro-7-methyloct-1-ene (3.4). Compounds 3.1 and 3.2 showed no cytotoxic activity against breast cancer cells. Another Portieria hornemannii sample was collected from Noordhoek in the Eastern Cape, it yielded one known compound referred to as 3Z-6-bromo-3-(bromomethylidene)-2,7- dichloro-7-methyloct-1-ene (3.5), as well as one new compound called portieric acid A (3.6) or 5-bromo-2-(bromomethylidene)-6-chloro-6-methylheptanoic acid. Portieric acid A showed slight cytotoxic activity and also represents a new class of compound within the genus Portieria. The isolation of secondary metabolites from the South African red alga, Laurencia glomerata, yielded two known compounds; 7-hydroxylaurene (4.9) and cis-neolaurencenyne (4.12), as well as one chamigrane related compound (4.11). Laurencia flexuosa yielded one known compound called 3Z-bromofucin (4.13). Using 1H NMR, GC and molecular systematics, a novel method for identifying different species of Laurencia was also investigated.
Keywords: Marine algae -- South Africa; Red algae -- South Africa; Pharmaceutical chemistry